Feroz ul lugaat urdu jaded: nai tarteeb aur izafoon ke sath (Feroz & Sons; Lahore)
"Feroz-ul-Lugaat Urdu Jaded: Nai Tarteeb aur Izafoon ke Sath" is an updated edition of the renowned Urdu dictionary, featuring a revised structure and additional entries for enhanced linguistic precision and modern usage.